Evaluating the effectiveness of brand activism as a marketing strategy on the purchase behavior of De La Salle University-Manila’s batch 117 ABM track senior high school students - Mones, Emma Lourdes R. (Animo Repository, 2019)
With the people's growing concern towards social, political, and environmental issues, people and businesses alike are taking a step towards solving issues through the use of brand activism, a form of corporate social responsibility. This study aims to determine the effectiveness of brand activism as a marketing strategy in relation to the purchase behavior of consumers, specifically ABM senior high school students of De La Salle University Batch 117. Additionally, this study aims to identify which factors have an effect on a consumer’s purchase behavior. In order to achieve this, the researchers gathered data from 103 students through the use of an online survey and from various relevant studies. The results of the survey show that brand activism has a positive effect on the purchase behaviour of the students. As for the factors that affect purchase behaviour, the data shows that socio-cultural factors, such as norms, conventions, customs, religion, festivity, social class, and lifestyle, have an effect on a consumer’s purchase behaviour. Aside from socio-cultural factors, the results also show that customer satisfaction with a brand’s product performance, service quality, and ability to meet their expectations has an effect on purchase behavior. Furthermore, personal beliefs and morals, family and friends, social trends, one's own advocacy, and convenience also affects a consumer’s purchase behavior. Lastly, the findings of the study suggest that brand activism, if done right, has the potential to motivate and encourage consumers to support a business’ social mission and also influence consumers to partake in initiating social change.